Enculturation of Art Value of Carving Decoration (Anthropological Studies of Preservation Efforts of Purwo Shadow Puppets in Wonogiri) - Subiyantoro, Slamet; Yusuf, Munawir; Zainnuri, Hasan (Sebelas Maret University, 2016)
This research tends to highlight the symbolic and philosophic values of Purwo shadow puppets. Most of the study themes though emphasize its exhibition. The objective of this study is to demonstrate the process of ongoing cultural art value of carving decoration in Wonogiri, in an effort to preserve the presence of Purwo shadow puppets. This case study was conducted in Kepuhsari village, Manyaran, Wonogiri, a village considered as the Purwo shadow puppets center long since generations before until now. This research uses a qualitative approach based a fixed distinct strategy. Data were collected through open interviews, observations and analysis of the documents/record contents. Then, they were analyzed using an interactive model starting from its collection, reduction process, then presentation and verification cycle. The results showed that the art value of carving decoration of Purwo shadow puppet in Wonogiri remains indelible and continues to exist until today since it has harmoniously been nurtured / cultured in a continuous way, whether in formal or non-formal education. Informal education implies learning activities undertaken at the masterâs, who is very knowledgeable in carving decoration, which tends to be social and freely performed at his home. Whereas formal ones, regarding civilizing value of carving decoration, take place at schools, where its materials are technically integrated at local culture programs and extra-curricular activities which are contracted in a planned but scheduled as well as cultivated by appointed instructors.